Working to reduce post-harvest loss - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Recent studies have shown that post-harvest losses in cassava crops occur in processing rather than in storage. The International Institute of Tropical Agriculture (llTA)'s Post-Harvest Technology Unit has carried out surveys on how to eliminate...